Research and Implementation of SVDU Simulator Based on Emulation Technology - Yanqun Wu; Mingxing Liu; Qi Chen; Xu Zhang; Xufeng Tian; Yu Zhang; Meiyuan Chen (Science and Technology of Nuclear Installations)
The safety video display unit (SVDU), as the display machine of the reactor protection system, performs the functions of displaying the reactor’s safety parameters and sending safety control commands. In order to meet the needs of nuclear power safety-level digital control system (DCS), like designing verification, operator training, and accidental drills, for the SVDU in the NASPIC platform developed independently by China National Nuclear Corporation, a virtual embedded system technology based on the micro x86 industrial host is proposed to make software simulation to the SVDU physical controller with exactly the same hardware appearance of the original one. The SVDU stimulator realized by this research can achieve 100% simulation of the logical functions of the SVDU physical equipment and the synchronized upgrading function between stimulator and the real equipment. With the development of multiple engineering application requirements, such as configuration verification and operator training, this stimulator has been applied in several virtual security level DCS projects.